Gendered climate change adaptation practices in fragmented farm fields of Gamo Highlands, Ethiopia. (20th April 2020) - Cholo, Tesfaye C.; Peerlings, Jack; Fleskens, Luuk
ABSTRACT: The objective of this study is to assess the existence of gendered climate change adaptation practices of smallholder farmers in the Gamo Highlands of Ethiopia. We hypothesized that smallholders' adaptation practices are gendered because of land fragmentation and gendered division of labour. To explore this, we considered sustainable land management practices as a tool for sustainable adaptation and assessed the effect of land management practices deployed and land fragmentation on intra-household time allocation. The results indicate that although land fragmentation increased hours worked by men and women significantly, fragmentation increased the working hours of men more than women. Application of a larger number of sustainable land management practices increases the mean working hours of women, but leaves unaffected the working hours of men, implying that adaptation practices are gender-biased. Therefore, this study can guide land management decisions by pointing out that fragmentation results in long working hours and adaptation practices may disproportionately affect women.